Diskursus Kriminalisasi Pemidanaan terhadap Pemberi Gratifikasi - Akbar, Muhammad Fatahillah (Jurnal Hukum & Pembangunan, 2025)
This article aims to examine the legal basis to prosecute gratifiers in Indonesian Corruption Justice System. Samin Tan as the giver of gratification to Eni Maulani Saragih had been acquitted by the Corruption Court of Jakarta Decision Number 37/Pid.Sus-TPK/2021/PN.Jkt.Pst on 30th August 2021. Then, the Cassation to Supreme Court had also been rejected by Supreme Court Decision Number 2205 K/Pid.sus/2022 on 9th June, 2022. Hence, Samin Tan stays acquitted. The decision majorly focuses on the “absence” of law which criminalizes gratifiers or gratification givers. Therefore, this article elaborates how similar cases shall be handled in the future. In answering the legal questions, there are crucial notes for KPK and also the court. From the beginning, Eni Maulani Saragih shall be indicted and convicted for bribery, not gratification. By doing so, the prosecution on the giver will not face such difficulties. Besides that, the court also considered that there is no particular article to prosecute gratifier, but briber. Howerver, Article 5 paragraph (1) letter a, letter b, and also article 13 of the Corruption act can also be applied to gratification giver. Article 12B for gratification receiver employes the wording “gratification as bribery”, so that those article may also apply for gratification receiver. This has also been proven in previous cases discussed in the Article.